Camouflage or Coincidence? Investigating the Effects of Spatial and Temporal Environmental Features on Feral Cat Morphology in Tasmania - Alexandra J. Paton; Barry W. Brook; Jessie C. Buettel (Ecology and Evolution)
ABSTRACT Variations in coat morphology are well documented among felids and are theorised to aid in camouflage during stalk and ambush hunting. A diverse array of coat types has arisen in Felis catus (feral cats) through domestication and subsequent selective breeding. This species has successfully spread across Australia over the past 200 years, raising the question of whether any specific coat types offer an adaptive advantage. We used 24,657 camera‐trap images of feral cats in Tasmania, Australia, and assigned each cat observation a coat colour and pattern. We analysed these data to examine how different spatial features affect the modal coat type present at a site. We also tested if cats with differing coat types were active on different days in response to temporal features, including moon luminosity (full or new). Elevation was positively associated with the presence of orange (odds ratio = 2.5, 97.5% confidence interval = 1.5, 4.4) and tortoiseshell (odds ratio = 4.1, CI = 1.6, 10.5) cats, while blotched brown cats were negatively associated with elevation (odds ratio = 0.64, CI = 0.5, 0.9), relative to black cats. Brown mackerel cats were more common in eucalypt and rainforests (odds ratio = 1.9, CI = 1.1, 3.3), as well as sites with a higher FPAR (odds ratio = 1.3, CI = 1.1, 1.6). All coat types were 1.2–2 times more likely to be active on nights with a new moon, except for orange cats who were equally active regardless of moon luminosity (odds ratio = 0.94, CI = 0.62, 1.42). Our results indicate that coat types are equally successful across Tasmania, perhaps owing to naïve prey or limited predator competition. The high activity of orange cats irrespective of moon phase may be reflective of the male cat's tendency to patrol territory, as opposed to favouring dark nights for hunting. Future studies should consider comparing the coat types found in feral cats to adjacent domestic populations, and against a wider array of habitat types to further investigate the potential for selective pressure on feral cat coat types in Australia.